Comparative pharmacokinetics of intravenous fentanyl and buprenorphine in healthy greyhound dogs. Issue 6 (29th March 2014) - KuKanich, B.; Allen, P.
<x xml:space="preserve">Abstract</x> The purpose of this study was to compare the pharmacokinetics of two highly protein‐bound, lipophilic opioid drugs. Fentanyl (10 μg/kg) and buprenorphine (20 μg/kg) were administered intravenously (IV) to six healthy greyhound dogs (three males and three females). The doses were based on clinically administered doses for dogs. Plasma drug concentrations were determined using liquid chromatography with mass spectrometry, and noncompartmental pharmacokinetics were estimated with computer software. The volume of distribution (area) was larger for fentanyl (7.42 L/kg) compared to buprenorphine (3.54 L/kg). The plasma clearance of fentanyl (38.6 mL·min/kg) was faster than buprenorphine (10.3 mL·min/kg). The terminal half‐life of fentanyl (2.22 h) was shorter than buprenorphine (3.96 h). Despite similar physicochemical properties including octanol–water partition coefficient and pKa, the pharmacokinetics of fentanyl and buprenorphine were not similar. Both fentanyl (84%) and buprenorphine (95–98%) are considered highly protein bound, but the differences in protein binding may contribute to the lack of similarity of pharmacokinetics in healthy dogs.